Dukungan Negara Arab Saudi Terhadap Pemerintah Tiongkok Dalam Isu Diskriminasi Etnis Uyghur di Republik Rakyat Tiongkok (RRT) - Niko Putra Arianta; Marten Hanura (Journal of International Relations Diponegoro, 2022)
"Ethnic Uyghurs are residents of the Xinjiang Region, Which is an ethnic minority in the People's Republic of China (PRC). There are subjevtive Chinese policies. Ethnic Uyghur are discriminated against by their own country and forced to slowly forget their true identity, namely Islam. Xinjiang where are attitude of Uyghur who seek justice and protest to the goverment, they are immediately arrested without going through a court process. Then,arrested Uyghur's are sent to re-education camps. The Chinese government's policy has received positive support from 37 countries and received and received negative support from 22 countries including Saudi Arabia. Saudi is the birthplace of Islam, which until now still uses the Shari'a system in state constitution. Saudi is an economically stable Islamic country and Saudi position should be the protector of Muslim in the Uyghur. But the similarities of identical does not ensure that Saudi to protect Uyghurs. This anomaly is the theme of this paper. This Paper was made by qualitative data. Through the Realism, This paper Analyzes Saudi Arabia's Foreign Policy which does not take a stand on this discrimination of Uyghur. Through 3 attributes of Realism namely ; Strength, Nationa Interest and Sovereignty, this paper try to illustrates that China's readliness to support the success of Saudi Vision 2030. Cause of this situation makes Saudi arabia not to take a stand to the Uyghur etnic group.''